Assessing the current state and restoration needs of the beaches and coastal dunes of Marismas Nacionales, Nayarit, Mexico. (December 2020) - Lithgow, Debora; Martínez, M. Luisa; Gallego-Fernández, Juan B.; Pérez-Maqueo, Octavio; Silva, Rodolfo
Highlights: The Mexican Biosphere Reserve Marismas Nacionales is affected by human activities. We studied the impact of artificial inlets and land use changes on the foredunes. Dune restoration priorities were identified using the ReDune index. The state of most foredunes is good, although threatened by human activities. Rehabilitation is urgently needed to protect human interests from storm impacts. Abstract: Around the world, population growth, land use changes and coastal infrastructure have modified coastlines. In many cases these actions have induced intense degradation and loss of the ecosystems there. Sandy beaches and coastal dunes are amongst the most threatened features. In Mexico, coastal dunes in the state of Nayarit, on the Pacific, have been affected by small scale tourism, the construction of artificial inlets and an increase in agricultural activities, even though they are part of a Biosphere Reserve. While there is a growing need for restoration or rehabilitation programs to protect these coastal dunes, such actions are almost non-existent because of financial limitations, difficulties in deciding which locations most urgently need these strategies, and the uncertainty of the results. Our goal was to evaluate the coastline of the Marismas Nacionales Biosphere Reserve, in the state of Nayarit, Mexico, examining geomorphological, ecological, and socioeconomic variables. Ninety sites were assessed, using the Re-Dune index, 41 beaches were found to be in a good state of conservation, while 43 are degraded but with the potential for success when subjected to restoration measures. Six sites were seen as highly degraded, with rehabilitation being the most viable option. By recovering the coastal dunes of Marismas Nacionales, the hurricane protection provided by them will be enhanced and sustainable social and economic development will be more likely.